Genetic resistance to gastrointestinal nematodes, with special reference to Haemonchus contortus, in three breeds of goats in Kenya - Shavulimo, R.S.; Rurangirwa, F.R.; Ruvuna, F.; James, A.D.; Ellis, P.R; McGuire, T. (1988)
An experiment was carried out to compare the susceptibility to haemonchosis of three breeds of goats and to seek indications of genetic resistance. Twelve East African, nine Galla and 13 East African X Toggenburg crosses were artificially infected with 500 Haemonchus contortus larvae per kg live weight. Liveweights, haematocrit and worm eggs were measured twice a week for 13 weeks. Clinical signs were recorded; postmortem and worm counts were done for animals which died. Mortality was lowest for East African (25%), intermediate for East African X Toggenburg. (46%) and highest for Galla (67%). Statistically, however, there were no signifIcant differences amongst the breeds in mortality rates, liveweights, haematocrit and egg counts. It was inferred that due to lack of challenge resulting from their selective (browsing) habits, goats have not been subjected to natural genetic selection for resistance to haemonchosis. The results of the present study and various studies relating to the selective feeding habits of goats are discussed.